Protection and Systemic Translocation of siRNA Following Oral Administration of Chitosan/siRNA Nanoparticles - Borja Ballarín-González; Frederik Dagnaes-Hansen; Robert A Fenton; Shan Gao; San Hein; Mingdong Dong; Jørgen Kjems; Kenneth A Howard (Elsevier, 2013)
Harnessing the RNA interference pathway offers a new therapeutic modality; however, solutions to overcome biological barriers to small interfering RNA (siRNA) delivery are required for clinical translation. This work demonstrates, by direct northern and quantitative PCR (qPCR) detection, stability, gastrointestinal (GI) deposition, and translocation into peripheral tissue of nonmodified siRNA after oral gavage of chitosan/siRNA nanoparticles in mice. In contrast to naked siRNA, retained structural integrity and deposition in the stomach, proximal and distal small intestine, and colon was observed at 1 and 5 hours for siRNA within nanoparticles. Furthermore, histological detection of fluorescent siRNA at the apical regions of the intestinal epithelium suggests mucoadhesion provided by chitosan. Detection of intact siRNA in the liver, spleen, and kidney was observed 1 hour after oral gavage, with an organ distribution pattern influenced by nanoparticle N:P ratio that could reflect differences in particle stability. This proof-of-concept work presents an oral delivery platform that could have the potential to treat local and systemic disorders by siRNA.